Oat production in Georgia - Nadiradze, Kakha (MTT, 2004)
Georgia is a country with an ancient tradition of land cultivation. In the 20th century it became an agro-industrial country. Traditionally Georgia has been a net exporter of food products and a major supplier of vegetables, fruit, tea, essential oils, citrus, wine, mineral waters, cognac, annual crops, cereals, (spring wheat, winter barley, winter rye, spring rye, oats, maize, beans, buckwheat, sugar-beet, sunflower, ground nut, Soya-bean, tobacco, cotton, potatoes, vegetables, vegetable crops, corn silage, folder root-crops, hay of perennial grass, hay of annual grass and vegetables. During recent years the supply of agricultural products from Georgia to the FSU republics and international markets has been substantially reduced. The country has lost its position on the export markets and as a result Georgia became a net importer of food products. More than 82 percent of GDP was produced by the private sector in 2002, compared to 74 percent in 2001. Today over 80 percent of agricultural production of cereales is in private sector. Georgia is divided into so called vertical zones. There are different physical, geographic and climatic conditions on this relatively small territory. We can come across almost all kinds of soil and climate existing in the world. With a long growing season and some areas of subtropical climate, cereals, (oats) citrus and a variety of deciduous fruits, vegetables and vine crops grow well along with tea, cereals, sunflower and a variety of field crops. With the variety of climates, almost any crop can be raised, giving Georgia one of the most diverse agricultural bases in our Southern Caucasus region. The agriculture industry is concerned primarily with the production of basic foodstuffs on farms but it also includes the supply of inputs for farming such as Oats seeds, cereals, begetables, fertilizers, animal feeds, and machinery. In addition, agriculture is becoming increasingly integrated with other sectors of the food chain such as processing, distribution and retailing to from the agri-food industry oats. K. Kelenjeridze Cereals Production in Georgia and Radiation factors of climate 1988.09.11 Tbilisi Georgia. G. Talakhadze Topsoils of Georgia 1990.07.11. Tbilisi Georgia. K. Nadiradze Oat Production in Georgia. 1997. 11.02 Tbilisi Georgia - Kvali (Journal of The Ministry of Agrioculture and Food of Georgia). E. Eristavi USAID. 1992.10.05 Tbilisi Georgia Tbilisi Georgia. FAO 2003.11.02 Tbilisi Georgia
Keywords: Ka; production; climate; crops